Sonority-Induced Vowel Deletion and Epenthesis in Bedouin Hijazi Arabic - AL SOLAMI, Majed (International Journal of Language and Literary Studies, 2024)
This paper examined vowel deletion triggered by sonority in Bedouin Hijazi Arabic. Bedouin Hijazi Arabic has a number of predictable vowel deletion processes that are phonologically conditioned. However, the type of vowel deletion examined in this paper is restricted in its application. It is triggered by sonority levels between a consonant in an onset position and a preceding coda. It results in word-medial clusters, which can trigger vowel epenthesis governed by the sonority hierarchy in the dialect. The epenthetic vowel varies in quality based on adjacent segments. The interaction between vowel deletion and epenthesis is examined within Harmonic Serialism, HS, a derivational framework of Optimality Theory. Instead of vowel deletion and vowel insertion taking place at all once, HS stipulates that only a single harmonic element is added progressively in each step. The same constraint hierarchy is implemented in each step until the desired output is achieved.